Penerapan Teknologi Dalam Manajemen Sumber Daya Pengelolaan Keuangan: Studi pada CV. Landel Elektrik Semarang - Sunarmi Sunarmi; Andhi Supriyadi; Bambang Guritno; Apri Kuntariningsih (Universitas Sains dan Teknologi Komputer, 2024)
Technological developments have changed the landscape in various sectors, including health, education and industry. However, its influence in Human Resource Management (HR) and financial management is still an important research topic. This research was conducted at CV. Landel Elektrik Semarang, a company engaged in the distributorship of electrical equipment. This project, which employs forty-three people, aims to investigate the relationship between the use of technology and the management of corporate finance and human resources. The analysis method involves path analysis and bootstrapping methods. The results show that, although the SDM shows a good level of reliability, problems of consistency between items within the construct surface. However, the application of technology and financial management shows higher validity. The results of the hypothesis test show that there is no relationship between human resources and the use of technology. However, there is a strong correlation between financial management and technology use. The implication of these findings is the importance of paying attention to technological factors in managing company finances, while improving the consistency and validity of human resources.